JOB-RELATED MOTIVATIONAL FACTORS AMONG MALAYSIAN EMPLOYEES - MANSHOR, AMAT TAAP (2002)
This study identified job-related motivational factors among Malaysian employees in several telecommunication companies. Responses were obtained from 1,179 employees at all levels up to senior managers and six different functional divisions, sales and marketing, human resources, finance, technical, information, technology, and support division. All employees were asked to rate the importance of Kovach's 10 job-motivational factors. These factors were good wages, job security, opportunity for career growth in the organization, good working conditions, interesting work, company loyalty to employees, tactful discipline, full appreciation of work done, sympathetic help with personal problems, and feeling of being involved in the organization. The top five factors employees identified as motivating them in their jobs were good wages, job security, company loyalty to employees, good working conditions, and full appreciation for work done. Findings were in accordance with Kovach for U.S. employees, in which the top motivational factors were good wages and job security.